CARA MEMILIH DAN MENGENALI INFORMASI OBAT - Larasati, Dwi (LPPM STIKES Madani, 2022)
Information about drugs must be owned by all levels of society. The increasing spread of counterfeit drugs and misuse of drugs is one of the efforts to increase public knowledge of getting, using, storing and disposing of drugs (DAGUSIBU) correctly. The purpose of this community service is to provide counseling to youth youth organizations in Nyamplung Srimulyo Village about how to read the information contained in the drug packaging when taking drugs, know about the kinds of drugs on the market and the differences (hard drugs, limited free drugs, over-the-counter drugs, mandatory pharmacy drugs), knowing about various kinds of drug preparations and how to use each to obtain the expected effect, knowing about the procedures for storing and disposing of drugs that are no longer used. This counseling is expected to increase knowledge of the use of drugs. This counseling was conducted out by lectures, discussions, leaflets and drugs along with drug packaging. Participants were given an example of how to read the information listed on the drug packaging when obtaining the drug. The results indicated that partisipantas began to understand to use the correct and appropriate drugs and read the information listed on the drug packaging.